A cross-cultural comparison: the socio-technical affordances of social media as a professional learning tool for teachers. Issue 5 (20th October 2021) - Prestridge, Sarah; Utami, Lokita Purnamika; Main, Katherine
ABSTRACT: Worldwide, teachers are connecting with each other, contributing ideas and curating resources through a range of social media platforms. Use of social media is framed within monocultural assumptions. As such, little is known about how different cultural values affect the way teachers reason and action online. This small-scale exploratory study focuses on ICT expert teachers' professional learning through social media and how socio-technical affordances predispose the way they engaged online. The socio-technical affordances include the relational interactions of the users, their capabilities and their intentions for the use of social media platforms. The study involved 15 teachers from Australia, Belgium and the USA. The findings present three categories that underpinned the ways teacher reasoned and actioned through social media with like-minded colleagues: non-competitive, competitive and adverse to competition. Cultural values at national and school level were found to influence how these teachers considered and enacted collaborative opportunities online.